IMPLEMENTING SELF-ASSESSMENT AND PEER ASSESSMENT THROUGH PORTFOLIOS - Sayidmurodova Shaxlo Otamurod qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines the implementation of self-assessment and peer assessment through the use of portfolios in educational contexts. Portfolios provide a structured framework for students to document their learning, reflect on their progress, and evaluate their own work critically. Additionally, portfolios enable peer assessment by allowing students to review, provide feedback, and learn from each other’s work. The study highlights strategies for integrating both self- and peer assessment into portfolio practices to enhance reflective thinking, critical evaluation, and collaborative learning. By employing portfolios as tools for assessment, educators can foster student autonomy, accountability, and comprehensive skill development.